Pencegahan Bullying di Sekolah Melalui Program “Welcome Day” - Budi Sarasati; Dian Kusumawati; Iin Wdiastuti (Universitas Muhammadiyah Surabaya, 2019)
This community service activity is motivated by the condition of problems in the environment of Junior High School (SMP) of Global Insani Islamic School (GIIS); it has been found that one of the problems that is deemed necessary to watch out is in terms of interaction with fellow Junior High School students. Based on the observation of the school, in this case is the teacher, the intercommunications of Junior High School students are considered